A biomechanical analysis of prosthesis disc in lumbar spinal segment using three-dimensional finite element modelling. (3rd June 2022) - Mabrouk, Mai S.; Marzouk, Samir Y.; Afify, Heba M.
Lumbar total disc replacement (LTDR) could be an operation for handling of chronic disc illness and spinal mutilation to safeguard a range of motion (ROM). The SB Charité™ is the principal gadget for LTDR however it creates a lot of confusion and long-run problems that lead to a lack of SB Charité™ disc. The advancement of lumbar disc arthroplasty supports the calculations of the biomechanical model through three-dimensional (3D) finite element method (FEM). Accordingly, this paper exhibits a 3D biomechanical FEM model of L1 to L3 human lumbar spine by various kinds of materials and discs. There are some criteria like compressive force, Tresca stress, von Mises stress and strain that are used to estimate the proposed model. This lumbar model instructs spinal surgeons to the predication vision for disc implementation which can consequently turn out recovery from disc degeneration and bolster the surgical outcomes. The COMSOL Multiphysics® software is applied on the intact segment and four implanted models that are Charité™, Activ-L, ProDisc-L and M6-L to determine the endurance and stiffness rate of vertebral endplate at each intervertebral disc.